How Verb Tense Shapes Persuasion - Packard, Grant; Berger, Jonah; Boghrati, Reihane (Journal of Consumer Research, 2023)
AbstractWhen sharing information and opinions about products, services, and experiences, communicators often use either past or present tense (e.g., “That restaurant was great” or “That restaurant is great”). Might such differences in verb tense shape communication’s impact, and if so, how? A multimethod investigation, including eight studies conducted in the field and lab, demonstrates that using present (vs. past) tense can increase persuasion. Natural language processing of over 500,000 online reviews in multiple product and service domains, for example, illustrates that reviews that use more present tense are seen as more helpful and useful. Follow-up experiments demonstrate that shifting from past to present tense increases persuasion and illustrate the underlying process through both mediation and moderation. When communicators use present (rather than past) tense to express their opinions and experiences, it suggests that they are more certain about what they are saying, which increases persuasion. These findings shed light on how language impacts consumer behavior, highlight how a subtle, yet central linguistic feature shapes communication, and have clear implications for persuasion across a range of situations.